Persistence of KIRneg NK cells after haploidentical hematopoietic stem cell transplantation protects from human cytomegalovirus infection/reactivation - Di Vito, Clara; Coianiz, Nicolò; Calvi, Michela; Terzoli, Sara; Zaghi, Elisa; Puccio, Simone; Frigo, Alessandro; Mariotti, Jacopo; De Philippis, Chiara; Mannina, Daniele; Sarina, Barbara; Mineri, Rossana; et al. (Frontiers in Immunology, 2024)
Haploidentical hematopoietic stem cell transplantation (h-HSCT) represents a therapeutic option to cure patients affected by hematologic malignancies. The kinetics and the quality of immunereconstitution (IR) impact the clinical outcome of h-HSCT and limit the onset of life-threatening Human Cytomegalovirus (HCMV) infection/reactivation. Natural Killer (NK) cells are the first lymphocytes that recover after h-HSCT and they can provide rapid innate immune responses against opportunistic pathogens. By performing a longitudinal single-cell analysis of multiparametric flowcytometry data, we show here that the persistence at high frequencies of CD158b1b2j neg /NKG2A pos /NKG2C neg /NKp30 pos /NKp46 pos (KIR neg ) NK cells is associated with HCMV infection/reactivation control. These KIR neg NK cells are "unlicensed" and not terminaldifferentiated lymphocytes appearing early during IR and mainly belonging to CD56 bright /CD16 neg and CD56 bright /CD16 pos subsets. KIR neg NK cells are enriched in oxidative and glucose metabolism pathways, produce interferon-γ and are endowed with potent antiviral activity against HCMV ex vivo.Decreased frequencies of KIR neg NK cells early during IR are associated with clinically relevant HCMV replication. Taken together, our findings indicate that the prolonged persistence of KIR neg NK cells after h-HSCT could serve as a biomarker to better predict HCMV infection/reactivation. This phenomenon also paves the grounds to optimize anti-viral immune responses by enriching posttransplant donor lymphocyte infusions with KIR neg NK cells.